The Influence of Village Funds and Cash Work Intensives on Village Economic Growth in Bone District - Haeril; Nurdin Brasit; Idayanti Nuryamsi (www.amertainstitute.com, 2025)
This research aims to analyze the influence of village funds and cash-intensive labor on the rate of village economic growth in Bone Regency. The background to this research is the existence of budget allocations from the APBN for village development since the promulgation of Law Number 6 of 2014 concerning Villages, which is expected to accelerate village development and improve the community's economy. This research provides an empirical contribution in understanding the mechanism of influence of village funds and Cash Work Intensives on village economic growth and provides policy recommendations to increase the effectiveness of village development in Indonesia.